"A True Newspaper Woman": The Career of Sadie Kneller Miller. Issue 1 (2nd January 2022) - Velloso, Carolina
ABSTRACT: This article examines the life and career of Sadie Kneller Miller, a journalist who enjoyed a thirty-year career as a baseball reporter, national and international correspondent, and photojournalist at the turn of the twentieth century. Her many accomplishments include being one of the first women to cover a sports beat for a newspaper, covering armed conflicts in Spanish-controlled Morocco, and obtaining exclusive interviews with figures such as Pancho Villa. Miller's career was also distinct in several important ways from those of most women journalists of her time, particularly in how she negotiated her professional ambitions with traditional gender roles. Miller earned a prominent contemporary reputation and left behind a rich collection of print and visual journalism, but her career has largely been lost to posterity. Using an unexplored and unprocessed archival collection, this article reconstructs Miller's career, emphasizing her most significant work in each journalistic function she performed, and shows the ways Miller both challenged and conformed to norms and expectations of women journalists of the period.